Academic Performance in Institutionalized and Noninstitutionalized Children: The Role of Cognitive Ability and Negative Lability - Mariana Sousa; Manuela Peixoto; Orlanda Cruz; Sara Cruz (MDPI AG, 2023)
More research is needed to understand the factors that contribute to low academic achievement in institutionalized children. The aim of this study was to investigate the relationship between cognitive and emotion regulation skills and academic performance, by comparing institutionalized and noninstitutionalized Portuguese children. The sample comprised 94 participants (46 institutionalized (22 boys) and 48 noninstitutionalized (23 boys) children), aged between 6 and 10 years, matched for age and sex. We used Raven's Colored Progressive Matrices (RCPM) to measure cognitive abilities. Emotional regulation and negative lability were assessed using the Emotion Regulation Questionnaire (ERC). Academic performance was assessed with the Competence Academic Scale (CAS) of the Portuguese version of the Social Skills Rating System-Teacher Form (SSRS-T). Institutionalized children exhibited poorer academic performance than their noninstitutionalized counterparts (effect size, η2 = 0.174). Cognitive ability (β = 0.28) and negative lability (β = −0.28) were significant predictors of academic performance. In addition to institutionalization, cognitive ability, and the challenges of managing negative emotions may contribute to the observed differences in academic performance. Interventions aimed at fostering cognitive and emotional competencies may play a protective role for institutionalized children facing academic and social difficulties.